Challenges of revenue generation in ASA local government area of Kwara state, Nigeria / Amin Amin ... [et al.] - Amin, Amin; Shittu, Raji; Ambali, Abdulrauf; Abdullahi, Alabi; Bamidele, Abdulrasheed Hamza (Research Management Centre (RMC), 2020)
The Asa local government area of Kwara State, Nigeria, is largely challenged by dwindling revenue generation leading to sustained budget deficits and paucity of funds for sustainable development of the area. This paper examined the income generation capacity of the local government and its implications for community development. The study used both primary and secondary data research methodology, which were interpreted and analysed. Findings from the study were that Asa local government generates insufficient revenues from both internal and external sources due to weak federal allocation and irregular remittance of its statutory financial allocation from the state joint account. The capacity of the local government to generate sufficient internal revenue is also challenged by poor tax collection capacity and enforcement policy and embezzlement of a large chunks of internally generated revenue by local government officials. The low revenue generation has reduced the construction of feeder road and community markets, and reduced drug supplies to the local government dispensary. The study concluded that Asa local government lacks adequate capacity to generate the required revenue for community development and recommended better training for the revenue collectors, improved political and financial autonomy for local governments and proper utilisation of revenue generated to improve community development in As a local government.